Les Mégalithes du département du Morbihan Structures Funéraires et Pierres Dresses - Gouézin, Philippe (Archaeopress, 2022)
Based on a corpus of architectural plans comprising 1413 megalithic monuments from the Department of Morbihan, including more than 250 unpublished monuments, this book aims at a better understanding of megalithism, or more precisely megalithisms, and presents a new approach to the relationship between standing stones (menhirs) and tombs (dolmens).